Technology and Transformation in Communication - K. R., Subramanian (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2018)
Recent technological advancements have had a drastic impact on the way individuals communicate. Many Research Findings suggest that technology has a negative effect on both the quality and quantity of face-to-face communication. Despite individuals’ awareness of the decrease of face-to-face communication as a result of technology, more than 62% of individuals observed on University campuses continue to use mobile devices in the presence of all. In response to the overwhelming presence of face time while viewing TV, several families have decided to implement a ban on video games, computers or smart phones. Due to the rapid expansion of technology, many individuals fear that people may be too immersed in the digital world and not present in the real world. People are becoming more reliant on communicating with friends and family through mobile phones and are neglecting to engage personally, uninhibited by phones and devices, in the presence of others. A majority of individuals felt the quality of their conversations degraded in the presence of devices, and many individuals were bothered when friends or family used technical devices while spending time together. Communication and collaboration play a big role in digital transformation.